Water Mitigation Effects on the Detonations in Confined Chamber and Tunnel System - H.Z. Zhao; K.Y. Lam; O.Y. Chong (Shock and Vibration)
The water mitigation effects on the detonations of explosive in a confined cube chamber are studied by use of a numerical code. Significant mitigation effects on shock pressure at various loading densities, various water/explosive mass ratios and various air gaps are obtained. Reduction of final static pressure is also obtained because water absorbs the energy released from the detonations through being compressed and vaporized. On the basis of this study, the detonations in a tunnel system with vent are further simulated. The numerical results are compared with the experimental data, and the water mitigation effects on shock pressure are verified.